2017
DOI: 10.1016/j.aju.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Can androgen-deprivation therapy obviate the need of channel transurethral resection of the prostate in advanced prostate cancer with urinary retention? A prospective study

Abstract: ObjectiveTo evaluate the efficacy of androgen-deprivation therapy (ADT) in relieving urinary retention in patients with advanced prostate cancer presenting with urinary retention or a high post-void residual urine volume (PVR).Patients and methodsPatients with advanced prostate cancer with an indwelling catheter for acute/chronic urinary retention, or with a high PVR (>200 mL) who had not received any previous treatment were included in the study. Patients with localised prostate cancer eligible for receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Conversely, a recently published study of metastatic PCa patients found that performing palliative TURP in addition to administering ADT, could significantly improve cancer-specific survival (CSS) compared with patients who only received ADT, when PSA ≥65 ng/ml, GS ≥8, and bone metastases ≤5 [13]. Although palliative TURP is the treatment of choice in patients with LUTS and PCa, only ADT can relief retention and decrease post voiding residual urine volume over a period of time, and can obviate the need for channel TURP in some patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recently published study of metastatic PCa patients found that performing palliative TURP in addition to administering ADT, could significantly improve cancer-specific survival (CSS) compared with patients who only received ADT, when PSA ≥65 ng/ml, GS ≥8, and bone metastases ≤5 [13]. Although palliative TURP is the treatment of choice in patients with LUTS and PCa, only ADT can relief retention and decrease post voiding residual urine volume over a period of time, and can obviate the need for channel TURP in some patients [14].…”
Section: Discussionmentioning
confidence: 99%